Sulla, the elites and the empire : a study of Roman policies in Italy and the Greek east - Santangelo, Federico. (Impact of Empire, 2007)
This book is a study of Sulla's policies in Italy and in the Greek East. Its main aim is to show how Sulla revived Rome's alliances with the local elites at a critical moment for the survival of her Mediterranean hegemony. The discussion calls into play a wide range of political, economic and religious issues, and the argument is developed from three complementary standpoints: role of elites, administration, and ideology. Sulla, the Elites and the Empire deals with both the impact of a prominent individual and the impact of the Roman empire. It sets outs to offer a new understanding of Sulla and his age and, more generally, to contribute to the understanding of the late Roman Republic.